Bi superlattice nanopolygons at BiOCl (001) nanosheet assembled architectures for visible-light photocatalysis. (May 2018) - Li, Yawen; Zhao, Yan; Wu, Gongjuan; Ma, Hongmei; Zhao, Jingzhe
Graphical abstract: Highlights: Bi superlattice nanopolygons at hierarchical BiOCl architectures were synthesized. BiOCl (001) architectures acted as the precursor and template of final products. The Bi/BiOCl samples displayed good photocatalytic activity on BPA degradation. Abstract: Bi superlattice structures at hierarchical BiOCl architectures were successfully synthesized via an in-situ reduction process. The nanosheet assembled BiOCl microflowers with exposed (001) facets acted as the precursor and template of complex architectures. Bi nanopolygons or nanodots were selectively formed at the surface of BiOCl nanosheets on controlling the reduction temperatures. Lamellar structure of BiOCl along [001] direction facilitates the homogeneous distribution of the reduced Bi particles in Bi/BiOCl architectures and induces the formation of superlattice structures. The Bi/BiOCl architectures with superlattice character as well as surface plasmon resonance (SPR) effect of Bi nanoparticles expand superior visible-light photocatalytic activity on colorless BPA degradation under guidance of RhB molecules.